Nonbilayer Phospholipid Arrangements Are Toll-Like Receptor-2/6 and TLR-4 Agonists and Trigger Inflammation in a Mouse Model Resembling Human Lupus. (19th October 2015) - Wong-Baeza, Carlos; Tescucano, Alonso; Astudillo, Horacio; Reséndiz, Albany; Landa, Carla; España, Luis; Serafín-López, Jeanet; Estrada-García, Iris; Estrada-Parra, Sergio; Flores-Romo, Leopoldo; Wong, Carlos; Baeza, Isabel
Abstract : Systemic lupus erythematosus is characterized by dysregulated activation of T and B cells and autoantibodies to nuclear antigens and, in some cases, lipid antigens. Liposomes with nonbilayer phospholipid arrangements induce a disease resembling human lupus in mice, including IgM and IgG antibodies against nonbilayer phospholipid arrangements. As the effect of these liposomes on the innate immune response is unknown and innate immune system activation is necessary for efficient antibody formation, we evaluated the effect of these liposomes on Toll-like receptor (TLR) signaling, cytokine production, proinflammatory gene expression, and T, NKT, dendritic, and B cells. Liposomes induce TLR-4- and, to a lesser extent, TLR-2/TLR-6-dependent signaling in TLR-expressing human embryonic kidney (HEK) cells and bone marrow-derived macrophages. Mice with the lupus-like disease had increased serum concentrations of proinflammatory cytokines, C3a and C5a; they also had more TLR-4-expressing splenocytes, a higher expression of genes associated with TRIF-dependent TLR-4-signaling and complement activation, and a lower expression of apoptosis-related genes, compared to healthy mice. The percentage of NKT and the percentage and activation of dendritic and B2 cells were also increased. Thus, TLR-4 and TLR-2/TLR-6 activation by nonbilayer phospholipid arrangements triggers an inflammatory response that could contribute to autoantibody production and the generation of a lupus-like disease in mice.